The flower morphology in three Convallariaceae species with various attractive traits - Odintsova, Anastasiya Valeryivna; Fishchuk, Oksana Sergyivna; Одінцова, Анастасія Валерівна; Фіщук, Оксана Сергіївна (Polish Botanical Society, 2017)
The general morphology and micromorphology of the flower in Polygonatum multiflorum, Maianthemum bifolium, and Convallaria majalis were studied using light microscopy methods. Among the studied species, P. multiflorum and C. majalis have syntepalous and trimerous flowers, and in M. bifolium flowers are the most reduced: they are dimerous, pentacyclic, and with free tepals. Only in P. multiflorum stamens are considerably adnate to the floral tube. The gynoecium of P. multiflorum consists of synascidiate, hemisymplicate, and asymplicate zones. In the gynoecium of M. bifolium and C. majalis, synascidiate, symplicate, and asymplicate vertical zones were revealed. In P. multiflorum and M. bifolium, the style is composed of postgenitally connated carpels, while in C. majalis the style is formed by congenitally fused carpels (symplicate gynoecium zone). A common pattern of the venation of the floral parts was revealed in all the species. The external flower morphology and the gynoecium inner structure are different in all three species, providing adaptations for the pollination mode. Attractive elements observed in the flower of P. multiflorum are the long septal nectary in the ovary and epidermal trichomes on the inner perigonium surface and on the filaments. In M. bifolium, a rudimentary external septal nectary was observed for the first time. No nectaries or other morphologically distinct secretory structures were found in the C. majalis flower, allowing considering the C. majalis flowers as pollen flowers.
Keywords: Convallaria majalis; Polygonatum multiflorum; Maianthemum bifolium; Nolinoideae; floral morphology; structural zones of the gynoecium; septal nectary